To the Question of the Efficiency of the Electron-Phonon Interaction in Lead Iodide Nanofilms - O.V. Pugantseva; V.M. Kramar (Журнал нано- та електронної фізики)
The question of the efficiency of the electron-phonon interaction in the formation of the electron, hole, and exciton energy spectrum in 2H-PbI2 semiconductor flat nanofilm is discussed. Based on the analysis of the theoretical calculation results of the bottom of the exciton energy band and its temperature dependence in nanofilms of different thickness, the optimal set of theory parameters which provides its agreement with the experimental measurement data is determined.